EDITORIAL - -, - (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2019)
We started the year 2019 with “Call for Papers” for publishing our 5th edition of Assumption University-eJournal of Interdisciplinary Research (AU-eJIR). Surprisingly, the response has been quite overwhelming.